If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2a = a + 12 Reorder the terms: 2a = 12 + a Solving 2a = 12 + a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1a' to each side of the equation. 2a + -1a = 12 + a + -1a Combine like terms: 2a + -1a = 1a 1a = 12 + a + -1a Combine like terms: a + -1a = 0 1a = 12 + 0 1a = 12 Divide each side by '1'. a = 12 Simplifying a = 12
| -28x-4(2x-5)= | | 2(2x+3)=2(x+15) | | 6=n^2+3n-12 | | 3(4x+2)=2y-4 | | 8x-4(2x-5)+2= | | -6(-w+3y-2)= | | (3x-2)(5x+1)(4)= | | 6+3q=15 | | 6=10-2w | | 5a-2b-8b+6a= | | 3-2r=2r | | 8x+14+2x=40-(9x+3) | | 2k-4=4 | | 2k-4= | | -10+7(a+3)=4(a-1)+5 | | f(-5)=0 | | 3x+22=4(x-1)-1 | | 1/7w=11 | | (-5)+(-7)= | | 3.67-(5.73+3)= | | 2(3x-5)=-7 | | 4x+7x=3x+5 | | 12x+8y=-1 | | 11x+7x+19=56 | | 10-2x-1= | | T^2-41=0 | | 5[3a-2a(3a+6b)+6a^2]= | | x-2y-3x+4y= | | 6+5y-3=9y+27-7y | | -6.58+12=-5.42 | | -2x-3(X+5)=14 | | 2[5(x+y)-2(3x-4y)]= |